2013
DOI: 10.1007/s10549-013-2622-y
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of gene expression-based biomarkers predicting outcome after tamoxifen treatment in breast cancer

Abstract: To date, three molecular markers (ER, PR, and CYP2D6) have been used in clinical setting to predict the benefit of the anti-estrogen tamoxifen therapy. Our aim was to validate new biomarker candidates predicting response to tamoxifen treatment in breast cancer by evaluating these in a meta-analysis of available transcriptomic datasets with known treatment and follow-up. Biomarker candidates were identified in Pubmed and in the 2007-2012 ASCO and 2011-2012 SABCS abstracts. Breast cancer microarray datasets of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
140
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(151 citation statements)
references
References 92 publications
6
140
1
Order By: Relevance
“…These data have been confirmed on MCF7 xenografts studies which also suggested specific gene expression profiles according to the resistance context, involving ER target genes as well as FOX family genes (3). Gene expression data obtained from clinical series of tamoxifen-treated patients confirmed a potential poor predictive value of a high expression of CXCL or SERPIN genes from which, we also identified in the TamR tumors (45). A parallel dynamic assessment was also performed in a small series of 15 letrozole-resistant patients, again pointing out the role of ER-responsive and proliferation genes in ET resistance, with striking individual variations (46).…”
Section: Discussionsupporting
confidence: 66%
“…These data have been confirmed on MCF7 xenografts studies which also suggested specific gene expression profiles according to the resistance context, involving ER target genes as well as FOX family genes (3). Gene expression data obtained from clinical series of tamoxifen-treated patients confirmed a potential poor predictive value of a high expression of CXCL or SERPIN genes from which, we also identified in the TamR tumors (45). A parallel dynamic assessment was also performed in a small series of 15 letrozole-resistant patients, again pointing out the role of ER-responsive and proliferation genes in ET resistance, with striking individual variations (46).…”
Section: Discussionsupporting
confidence: 66%
“…5F; refs. 24,30). This prognostic effect was not observed in patients with ERanegative tumors ( Supplementary Fig.…”
Section: Spen Sensitizes Era-positive Breast Cancer Cells To Tamoxifenmentioning
confidence: 85%
“…For IHC, the correlations between PDE5 and grading/ER/PR/HER2 status were examined with MannWhitney U test, between PDE5 and breast cancer subtypes by Kruskal-Wallis test (GraphPad Prism4). Kaplan-Meier survival plot, HR with 95% CIs and log-rank P values were calculated and plotted in R as described (33). Cox proportional hazard regression was computed to compare the association between gene expression, clinical variables including ER/HER2/lymph node status, and survival in multivariate analysis using Win-STAT 2014 for Microsoft Excel (Robert Fitch Software).…”
Section: Discussionmentioning
confidence: 99%